Effect of Minho estuarine plume on Rias Baixas: numerical modeling approach - Sousa, Magda C. (2018)
The Minho River, situated 30 km south from the Rias Baixas, is the most important freshwater source flowing into the Western Galician coast. This discharge is particularly important in driving the circulation and hydrography of this coastal region. To study this important issue, numerical modeling may constitute an important tool being used to understand the coastal plume effects under different conditions. The main purpose of this study is to implement and validate a marine model able to reproduce the propagation of the Minho estuarine plume. The chosen period for the validation was the spring of 1998, because a high Minho River discharge was reported as well as favorable wind patterns to spread the river plume towards the Rias Baixas. The numerical model MOHID was used through a downscaling approach with a three-level one-way nested scheme. The numerical predictions show good agreement with the observed water level in the entire domain. Also, the measured components of the velocity are well represented by the model, as well as the observed pycnocline, which is predicted for the observed depth. According to the model results, a buoyancy intrusion caused by the Minho river reverses the normal estuarine salinity longitudinal gradient of the Rias de Vigo and Pontevedra. Otherwise, this pattern is not observed in the Ria de Arousa. All these patterns are corroborated by in situ measurements. In summary, the validation results show that the model adequately reproduces the hydrodynamic and thermohaline patterns of the Western Galician coast.